Healthy immigration effect among internal migrants in megacities: a cross-sectional study in Shanghai, China - Enhong Dong; Enhong Dong; Enhong Dong; Ting Xu; Ting Xu; Jiahua Shi; Dongjiao Ba; Haiwang Zhou; Zhijian Li; Cheng Huang; Cheng Huang (Frontiers Media S.A., 2023)
ObjectivesTo verify the healthy immigration effect on self-rated health (SRH) among Chinese internal migrants, identify the determinants of SRH, and provide recommendations for the Chinese government to formulate effective intervention strategies to improve population governance and health management in megacities.MethodsA sample comprising 1,147 white-and blue-collar migrant workers was randomly selected through an online survey conducted in Shanghai from August to December 2021. Multivariate logistic regression models were used to verify the healthy immigration effect as well as determinants of the effect among internal migrants in Shanghai.ResultsAmong 1,024 eligible internal migrants, 864 (84.4%) were aged between 18 and 59 years, 545 (53.2%) were men, and 818 (79.9%) were married. When confounders in the logistic regression models were adjusted, the odds ratio of SRH for internal migrants who had lived in Shanghai for 5-10 years was 2.418 (p < 0.001), whereas the odds ratio for those who had lived there for ≥10 years was not statistically significant. Additionally, marital status, a postgraduate or higher degree, income level, number of physical examinations in the past 12 months, and the number of critical diseases they were suffering from, were significant contributing factors for favorable SRH among the internal migrants. Furthermore, a cross-sectional analysis revealed that SRH demonstrated a healthy immigration effect among blue-collar internal migrants from the manufacturing industry but not among white-collar internal migrants.ConclusionA healthy immigration effect was observed among internal migrants in Shanghai. The migrant population that had lived in Shanghai for 5-10 years had more health advantages than the locals, whereas those who had lived there for ≥10 years did not. The Chinese government should understand this effect and enact measures accordingly, such as implementing physical examinations, improving acculturation, addressing individual characteristics, and improving socioeconomic conditions to improve the physical and mental health of internal migrants. Enacting such changes could facilitate the integration of migrants into the local culture of megacities.